Figural Realism Studies in the Mimesis Effect - White, Hayden (Johns Hopkins University Press, 2020)
Originally published in 1998. In his earlier books such as Tropics of Discourse and The Content of the Form, Hayden White focused on the conventions of historical writing and on the ordering of historical consciousness. In Figural Realism, White collects eight interrelated essays primarily concerned with the treatment of history in recent literary critical discourse. "'History' is not only an object we can study," writes White, "it is also and even primarily a certain kind of relationship to 'the past' mediated by a distinctive kind of written discourse. It is because historical discourse is actualized in its culturally significant form as a specific kind of writing that we may consider the relevance of literary theory to both the theory and the practice of historiography."